Awareness of Consumer Protection Act among medical and dental professionals - a cross sectional study from Davangere, Karnataka, India - Ramachandrappa, Shwetha; Sathyanarayan, Vivek (Journal of Biomedical Sciences, 2015)
Background: Enormous scientific and technological advancements, reduced the mortality rate, morbidity but certain issues came up, which significantly affected the trust and relationship between a doctor and the patient such as, deteriorating quality of medical education, ethical issues, commercialization of medical fields and corporate culture for patient management. So it is important to know about the consumer protection act (CPA). The purpose of this research was to assess the awareness of CPA among Dental and Medical practitioners in Davangere city, Karnataka, India. Methods: 504 dental and medical professionals were included in the survey. A self?administered, structured questionnaire written in English script, validated through a pretested survey including 22 items was used to evaluate the awareness and practices regarding CPA among all the participants. Results: The results showed that there was no significant difference in awareness regarding COPRA among medical professionals and dental professionals. In this study we observed private practitioners had more awareness comparing with the doctors associated with the academic sector. Conclusion: Medical and dental professions need to update their understanding on consumer protection act and its amendments to be on a legally safer side. DOI: http://dx.doi.org/10.3126/jbs.v1i3.12474 J. Biomed Sci. 2014, 1(3):14-19